Risk of cardiovascular diseases after breast cancer: an analysis on a cohort of 1.3 million women. (13th November 2019) - Ricceri, F; Calabrese, S C; Ferracin, E; Di Cuonzo, D; Macciotta, A; d'Errico, A; Franco, P F; Numico, G; Pagano, E; Sacerdote, C
Abstract: Background: Breast cancer (BC) is the malignant tumor with the highest incidence in women in the world with an estimate of about 500, 000 new cases per year in Europe. Guidelines for BC treatment include surgery followed by radiotherapy, hormonal therapy or chemotherapy. Several studies showed that BC treatment increases the risk of myocardial infarction (MI) while only few studies investigated the risk of stroke after BC. The aim of the present study was to assess the risk of MI and stroke in BC survivors, taking into account the possible influence of treatments. Methods: Women included in the study are part of a longitudinal cohort including all residents in the Piedmont region linked to the 2011 census data and followed-up through administrative data on mortality, hospital admissions, drug prescriptions, and outpatient consultations. Validated algorithms to identify BC incident cases and their therapies as well as to identify MI and stroke were applied. The effect of BC on the risk of MI and stroke was tested using Cox models (adjusted for confounding variables) that allow to account for the competing risks. First, BC patients were compared to healthy women, then BC women that undertwent a specific therapy were compared with both healthy women and other BC patients. Results: Women with BC showed an increased risk compared to healthy women for both MI (HR: 1.20; 95% CI: 1.05-1.38) and stroke (HR: 1.58; 95%CI: 1.38-1.82). Chemotherapy almost doubled the risk of MI, while radiotherapy did not seem to have a similar effect, even comparing with other BC patients. The high risk of stroke observed comparing BC (any therapy) with healthy women disappeared when comparing specific therapies among BC patients. Conclusions: Chemotherapy increased the risk of MI in BC patients, while recent radiotherapy strategies had less impact, if any. Moreover, the mechanism for which BC patients have an increased risk of stroke seems not to be related to a late effect of therapies. Key messages: Breast cancer women are at higher risk of developing cardio and cerebrovascular diseases and this should be taken into account when planning therapies and follow-up surveillance. Despite the increase in quality of the therapeutic approaches for breast cancer patients, chemotherapy increases the risk of myocardial infarction, while radiotherapy dangerousness recently decreased.